Association of Neutrophil-Lymphocytes Ratio (NLR) and D-Dimer Levels with COVID-19 Mortality - Ramadhan, Muhammad Aidil Aulia; Sawitri, Endang; Wahyunie, Sri (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Coronavirus Disease 2019 (COVID-19) is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Due to the severity and transmission of SARS-CoV-2, exploration of risk factors for mortality in COVID-19 patients as early as possible becomes very important for appropriate actions and interventions and to improve the cure and quality of prognosis of COVID-19 patients. This study aimed to determine association of NLR and D-dimer with COVID-19 patient mortality. An analytical observational study with a cross-sectional study approached using 90 data from medical records of adult COVID-19 patients who were hospitalized at Abdoel Wahab Sjahranie Hospital Samarinda from July to December 2021. Statistical analysis using Spearman’s correlation, p <0,05 was significant. The results showed male patients = 51 and female patients = 39. The mean age of survived patients = 52 years and deceased patients = 50 years. Median neutrophil count of survived patients = 5.5 x 103/μl and deceased patients = 6.95 x 103/μl. Median lymphocyte count of survived patients = 1.11 x 103/μl and deceased patients = 1.03 x 103/μl. Median NLR of survived patients = 4.99 and deceased patients = 6.14. The median of D-dimer level of survived patients = 1.08 μg/ml and deceased patients = 1.83 μg/ml. The association of NLR with COVID-19 mortality showed p = 0.031; r = 0.228. The association of D-dimer levels with COVID-19 mortality showed p < 0.001; r = 0.416. It was concluded that NLR and D-dimer levels each had a significant relationship with mortality in COVID-19 patients.